Looking at the Process: Examining Creative and Artistic Thinking in Fashion Designers on a Reality Television Show - Hogan, Jillian; Murdock, Kara; Hamill, Morgan; Lanzara, Anastasia; Winner, Ellen (Frontiers in Psychology, 2018)
We examine creativity from a qualitative process rather than a quantitative product perspective. Our focus is on “habits of mind” (thinking dispositions) used during the creative process, and the categories we used were those of the eight Studio Habits of Mind observed in visual arts classrooms (Hetland et al., 2007, 2013). Our source of data was footage from a popular reality television show, Project Runway, in which nascent fashion designers are given garment design challenges. An entire season of the show (14 episodes) was transcribed and coded for the presence of eight Studio Habits of Mind. We found abundant evidence of all eight of these thinking dispositions in all portions of the show. We argue that the creative thinking occurring during fashion design bears strong resemblances to that which occurs in the art studio-classroom. Qualitatively created frameworks, like those of the Studio Habits of Mind, can be used to inform our understanding of creative behavior in various disciplines.